2015
DOI: 10.1007/s00408-015-9813-8
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of CT Metrics in Chronic Obstructive Pulmonary Disease with Pulmonary Hypertension

Abstract: Our study demonstrates that the use of quantitative CT analysis is a plausible and beneficial tool for predicting and evaluating the effect of pulmonary vasodilators in patients with COPD-PH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
0
11
0
2
Order By: Relevance
“…In addition, CT might also provide relevant information on the extent of emphysema and airway wall disease, which for instance could be of use in determining treatment effect. Ando et al showed in a small set of COPD subjects that the automated quantification of emphysema and the extent of small pulmonary vessels is associated with a treatment effect of pulmonary vasodilators [ 29 ]. Assessing emphysema on CT might also be used to better understand the reduced aerobic exercise capacity in lung transplants candidates with COPD and PH.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CT might also provide relevant information on the extent of emphysema and airway wall disease, which for instance could be of use in determining treatment effect. Ando et al showed in a small set of COPD subjects that the automated quantification of emphysema and the extent of small pulmonary vessels is associated with a treatment effect of pulmonary vasodilators [ 29 ]. Assessing emphysema on CT might also be used to better understand the reduced aerobic exercise capacity in lung transplants candidates with COPD and PH.…”
Section: Discussionmentioning
confidence: 99%
“…Except for prediction of COPD exacerbations, [ 11 ] the clinical implications of our results remain largely unknown. Ando et al [ 39 ] evaluated the role of quantitative CT in determining the effect of pulmonary vasodilators in COPD patients with pulmonary hypertension and concluded that quantitative CT analysis is a plausible and beneficial tool. If an elevated PA:AA ratio is a reliable surrogate for pulmonary hypertension, it may represent a useful parameter for the diagnostic screening of patients for right heart catheterization and before considering therapy with vasodilators or other treatments aimed at the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…The technological evolution of CT devices and computer analysis programs allowed the development of objective, quantitative tools for analysis of the lung parenchyma (in cases of emphysema or fibrosis), the airways (in cases of chronic obstructive pulmonary disease, asthma, or cystic fibrosis), and, more recently, the pulmonary vessels. Some studies, such as that conducted by Ando et al ( 23 ) , have demonstrated the potential of quantitative evaluation of the pulmonary vasculature for the detection of the effect of treatment with vasodilators in patients with chronic obstructive pulmonary disease and PH.…”
Section: Discussionmentioning
confidence: 99%